Integrating Employee Well-Being into HRM for Effective Distance Working Implementation - Dody Suhermawan; Almira Vidhayandika M (PT. Mawadaku Sukses Solusindo, 2025)
Purpose - The growing adoption of remote work has raised important questions regarding the role of human resource management (HRM) practices in safeguarding employee well-being. While well-being-oriented HRM has been recognized as an essential framework for supporting happiness, health, and social connectedness in traditional organizational settings, its relevance in remote work arrangements remains ambiguous. The reduced physical presence and visibility of employees in remote contexts may diminish the effectiveness of such practices, thereby warranting a deeper empirical investigation. Aims - This study seeks to examine whether well-being-oriented HRM maintains its capacity to enhance employee well-being in remote working environments, as compared to conventional, on-site contexts. More specifically, it aims to evaluate how distinct domains of well-being-oriented HRM are associated with different facets of employee well-being—including psychological well-being (happiness, job satisfaction, and engagement), physical well-being (strain and health), and relational well-being (social connectedness). Additionally, the moderating role of remote work intensity is assessed to determine whether variations in the extent of remote work influence these relationships. Design - The empirical analysis was conducted using a two-wave dataset collected from 258 Indonesian state-owned manufacturing enterprises. By differentiating between remote and non-remote work settings, the study applies a comparative lens to assess both the direct associations of well-being-oriented HRM with well-being outcomes and the potential moderating influence of remote work intensity. This approach allows for a nuanced understanding of how HRM practices function across varying organizational work arrangements. Findings - The results indicate that well-being-oriented HRM continues to exert a positive influence on employee well-being in remote work contexts, particularly in terms of happiness (engagement and job satisfaction) and health (strain reduction). However, variations emerge across domains of HRM, as certain practices appear more effective in enhancing happiness and health-related outcomes than others.